Teaching Science Communication to Master’s Students in STEM - Julian Fick; Friederike Hendriks; Noemi Kumpmann; Barbara Thies (European Journal of Psychology Open)
Abstract: Introduction: In times of crisis like COVID-19, science communication is a means to provide orientation to the public. Science communication places high demands on the capabilities of those who conduct it, and, thus, interventions should be developed and evaluated for their effectiveness. Aim: This paper introduces an intervention to support science communication knowledge, attitudes, self-efficacy, and performance. The manualized one-day training program covered communication basics and specific strategies to enhance comprehensibility, involvement, and credibility in communication. Method: In developing the intervention, we used a constructive alignment approach, resulting in closely linked evaluation, instructional methods (including peer and video feedback), and content. 16 STEM master’s students attended the training program. Results: The evaluation revealed an increase in participants’ knowledge, their positive attitude toward science communication, and self-efficacy beliefs. Coding videos from short presentations additionally revealed an increase in involvement strategy usage but not in comprehensibility or credibility strategy use. Discussion: While we confirmed the overall effectiveness of the intervention, we also discuss the challenges that emerged with assessing the performance and evaluating the evidence. Further, we discuss how psychology can support the handling of public crises through education and by fostering researchers’ science communication skills.